2012
DOI: 10.1097/lgt.0b013e31825d2d7a
|View full text |Cite
|
Sign up to set email alerts
|

Anal Intraepithelial Lesions in Women With Human Papillomavirus–Related Disease

Abstract: Immunocompetent women with CIN, vaginal intraepithelial neoplasia, or VIN may also present high-grade or low-grade anal intraepithelial lesions so we should consider AIN as part of multicentric disease of the lower genital tract. Cervical intraepithelial neoplasia, VIN, condyloma accuminatta, and vaginal intraepithelial neoplasia could be warning signs of anal intraepithelial lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 15 publications
3
24
1
4
Order By: Relevance
“…This is similar to the prevalence in other low-risk populations (3.9%-10%), [15][16][17] but lower than the prevalence of AIN reported in other high-risk populations (19.6%-28%), such as those with genital dysplasia or a history of transplant. 16,18,19 However, the trend toward a higher prevalence of ASC-US in IBD patients is in keeping with the cervical dysplasia literature. Kane et al 11 studied 40 patients with IBD and compared with matched controls found the prevalence of cervical dysplasia to be higher in patients with IBD vs those without (42.5% vs 7%; P < .001).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This is similar to the prevalence in other low-risk populations (3.9%-10%), [15][16][17] but lower than the prevalence of AIN reported in other high-risk populations (19.6%-28%), such as those with genital dysplasia or a history of transplant. 16,18,19 However, the trend toward a higher prevalence of ASC-US in IBD patients is in keeping with the cervical dysplasia literature. Kane et al 11 studied 40 patients with IBD and compared with matched controls found the prevalence of cervical dysplasia to be higher in patients with IBD vs those without (42.5% vs 7%; P < .001).…”
Section: Discussionsupporting
confidence: 66%
“…This was low compared with other studies in which 32% to 47% reported receptive anal intercourse. 18,19 Receptive anal intercourse is a well-established risk factor for AIN 15,16,18 and low reporting rates may explain why our study could not verify this as a risk factor.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…39,47-49 A small study compared 33 immunocompromised (included 16 women with HIV and 7 women with a transplant, lupus, or diabetes) and 304 immunocompetent women referred for colposcopic evaluation because of an abnormal cervical cytology or a genital lesion. 47 The evaluation included a concurrent HRA.…”
Section: Anal Hpv Infection and Disease In Womenmentioning
confidence: 99%
“…A study of 481 women with LGTN (235 with CIN, 92 with VaIN, and 227 with VIN) was reported by Tattiet al 49 All women were evaluated by anal cytology, HRA and biopsy of any suspicious lesions. Of the entire study population, 404 (84.0%) were immunocompetent, 31 (6.4%) were HIV-infected, and 46 (9.6%) were immunosuppressed from other causes.…”
Section: Anal Hpv Infection and Disease In Womenmentioning
confidence: 99%